Hukum pembuktian di peradilan agama - Supramono, Gatot, 1953- (Bandung : Alumni, 1993)
Law of evidence in cases at Islamic courts in Indonesia
Includes bibliographical references (p. 131-132)
Keywords: Evidence (Law) -- Indonesia; Evidence (Islamic law) -- Indonesia